2022
DOI: 10.1037/ppm0000371
|View full text |Cite
|
Sign up to set email alerts
|

Consuming memes during the COVID pandemic: Effects of memes and meme type on COVID-related stress and coping efficacy.

Abstract: As COVID-19 quickly spread across the globe, social media memes (i.e., typically humorous or cute images related to popular culture) about life in a pandemic also spread across the Internet. We conducted a between-subjects online experiment (N = 748) to assess how viewing memes during this pandemic era may influence audiences' stress and coping. In terms of psychological responses, we found that meme viewing (vs. nonmeme content) was associated with stronger cuteness responses, higher levels of reported humor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
(19 reference statements)
0
15
0
1
Order By: Relevance
“…Possible benefits of mental health memes Members of the general population display increased positive emotional responses when observing humorous internet memes, relative to other forms of online media (Myrick et al, 2021). In the current context, a culmination of research highlights perceived benefits associated with online interaction with mental health memes (Akram et al, 2020;Drury, 2019;Gardener et al, 2021;Kariko and Anasih, 2019).…”
Section: Key Concernsmentioning
confidence: 91%
See 1 more Smart Citation
“…Possible benefits of mental health memes Members of the general population display increased positive emotional responses when observing humorous internet memes, relative to other forms of online media (Myrick et al, 2021). In the current context, a culmination of research highlights perceived benefits associated with online interaction with mental health memes (Akram et al, 2020;Drury, 2019;Gardener et al, 2021;Kariko and Anasih, 2019).…”
Section: Key Concernsmentioning
confidence: 91%
“…Internet memes related to non-traumatic situational work experiences are evidenced to help emergency medical service providers cope with work-related stress and burnout (Drury, 2019). Furthermore, anxious individuals observe memes related to the COVID-19 pandemic to cope with an uncertain and anxiety provoking situation Myrick et al, 2021). In a sample of the US general population, Myrick and colleagues (2021) found the observation of COVID captioned memes to be associated with reduced COVID-related stress relative to those observing memes unrelated to the pandemic.…”
Section: Key Concernsmentioning
confidence: 99%
“…Social media has become an important source of information (Bradley et al, 2019). Myrick et al (2021) recently examined the effects of viewing social media memes and found that memes with captions relating to the COVID-19 pandemic led to deeper information processing. According to Thom-Santelli et al (2011), junior-level employees working at IBM used its social networking site more frequently than others to process information on culture and values.…”
Section: Employee Communication Behavior On Social Mediamentioning
confidence: 99%
“…Other studies dedicated to the effects of political memes found that the consumption of memes has positive effects on users' political engagement (Zhang and Pinto, 2021;Johann, 2022) and that the memetic presentation of credible information results in higher levels of engagement, such as commenting and sharing political memes (Wasike, 2022). Moreover, studies inside and outside the political context have shown that memes trigger users' emotions and subtle perceptions of the presented messages (Williams et al, 2016;Akram et al, 2020;Gardner et al, 2021) and that humor plays an important role as an enabler of cognitive and affective outcomes (Gardner et al, 2021;Myrick et al, 2021;Wong and Holyoak, 2021).…”
Section: Political Internet Memes and Memeified Politicsmentioning
confidence: 99%